SAT0179 ADHERENCE TO HYDROXYCHLOROQUINE INFLUENCES THE INCIDENCE OF ORGAN DAMAGE DURING FOLLOW-UP IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Kang, J. H.; Choi, S. E.; Xu, H.; Park, D. J.; Lee, S. S.
Abstract : Background: Objectives: Hydroxychloroquine (HCQ) is a cornerstone drug in patients with systemic lupus erythematosus (SLE), decreasing the risk of flares and comorbidities and improving survival. This study investigated the effects of HCQ adherence on clinical manifestations, disease activity, and organ damage in Korean patients with SLE. Methods: Data on 299 SLE patients were obtained from the Korean Lupus Network registry. Demographic variables, clinical manifestations, laboratory findings, PGA, and SLEDAI-2000 and SLICC damage index scores were recorded at the time of enrollment and repeated annually for 4 consecutive years. Patients were divided into two groups according to the level of HCQ adherence. Adherence was defined by the medication possession ratio and dichotomized as ≤ 80% vs. > 80%. Univariate and multivariate analyses were performed to assess the impact of adherence to HCQ on clinical outcomes. Results: Of the 299 patients, 31 (10.4%) showed poor drug adherence during the follow-up period. Patients with poor HCQ adherence were older (P=0.011), less insured (P=0.024), experienced lower employment (P=0.033), and had a higher rate of comorbidities such as hypertension (P=0.048) and depression (P<0.001). The non-adherent group had higher mean and changed SLICC damage index scores than the adherent group across all 4 years. In the multivariate analysis, HCQ non-adherence was significantly associated with older age (OR, 1.043; 95% CI, 1.006–1.081; P=0.021), depression (OR, 11.98; 95% CI, 1.099–130.6; P=0.042), and an annual increase in the SLICC damage index score (OR, 2.275; 95% CI, 1.369–3.779; P=0.002). Conclusion: HCQ adherence might be influenced by age and depressive mood. Additionally, the poor adherence to HCQ in SLE patients was correlated with higher cumulative organ damage. Therefore, patients with SLE should be educated to take HCQ appropriately to improve their clinical outcome in clinical practice. Disclosure of Interests: None declared